Robust microwave absorption in silver-cobalt hollow microspheres with heterointerfaces and electric-magnetic synergism: Towards achieving lightweight and absorption-type microwave shielding composites. (1st March 2023) - Yang, Dian; Tao, Jun-Ru; Yang, Yi; He, Qian-Ming; Wang, Ming
Highlights: Silver-cobalt hollow microspheres are successfully prepared. Silver-cobalt hollow microspheres show excellent microwave absorption. An effective absorption bandwidth of 8.40 GHz is achieved. Silver-cobalt hollow microspheres endow absorption-type shielding materials. Silver-cobalt hollow microspheres give the composites a low density. Abstract: Lightweight and high-efficiency microwave shielding materials based on high absorption loss are the hotspot of current research. Herein, the silver-cobalt bimetallic hollow microspheres (Ag-Co-HM) with low reflection loss and broadband absorption efficiency were fabricated and then used to construct bimetallic hollow structures in polydimethylsiloxane/carbon nanotube composites (PDMS/CNT) to obtain the lightweight and absorption-type microwave shielding composites. The microwave absorption of Ag-Co-HM and the microwave shielding effectiveness (SET ) of the PDMS/CNT/Ag-Co-HM composites was evaluated and discussed. The Ag-Co-HM with a molar ratio (Co/Ag) of 2.07 exhibited a low reflection loss as –46.6 dB at a thickness of 2.6 mm, and an effective absorption bandwidth of 8.40 GHz. The SET of the PDMS/CNT composites was greatly enhanced by the incorporation of the Ag-Co-HM. Furthermore, the absorption coefficient ( A ) was also improved by adding the Ag-Co-HM and was much higher than the reflection coefficient. The composites exhibited absorption-type microwave shielding composites. For example, the average microwave SET of 59.4 dB and A value of 0.78 are achieved in the PDMS/CNT/Ag-Co-HM composites containing 5 wt% CNTs and 10 wt% Ag-Co-HMs, which are much higher than the corresponding values of 33.7 dB and 0.63 in the PDMS/CNT composites with only 5 wt% CNTs. In addition, the hollow structure of Ag-Co-HM endows the PDMS/CNT/Ag-Co-HM composites to have a low density. Graphical abstract: Image, graphical abstract